PENERAPAN METODE URBAN AKUPUNKTUR DALAM PERANCANGAN WADAH KOMUNITAS DI KALIANYAR, JAKARTA BARAT - Eric Manzo Bewintara; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2022)
The number of slum settlements in Jakarta has increased dramatically, according to the Central Statistics Agency, slum settlements in Jakarta in 2017 were 14.55%, in 2018, 14.33% and in 2019 the number rose drastically to 42.73%. These slum settlements increase the potential for many diseases, such as dysentery, diarrhea, tuberculosis, malaria and typhus. These diseases not only cost the country 50 trillion, but also contribute to 88 percent of child deaths in Indonesia. One of the settlements in West Jakarta that has health problems is Kalianyar. The population density and building density in this village are very high. This results in poor environmental sanitation, air circulation and natural lighting in residential areas that are built close together. The high morbidity rate has an impact on the quality of life in this village. This paper presents the results of qualitative research on the physical condition of the environment and the socio-economic and health aspects of slum dwellers in Kalianyar. The aim of the study is to produce solutions to the problems mentioned above using an urban acupuncture approach. The analysis carried out resulted in solutions in the form of providing a community forum which in addition to being a place for education and community interaction, also became an integrated clinic facility, to improve public health in Kalianyar. Keywords: Diseases; Slums; Urban Acupuncture; Wellness Centre Abstrak Jumlah pemukiman kumuh di Jakarta naik drastis, menurut Badan Pusat Statistik, pemukiman kumuh di Jakarta pada tahun 2017 adalah 14.55%, pada tahun 2018, 14.33%dan pada tahun 2019 angka naik dengan drastis ke 42.73%. Pemukiman yang kumuh ini meningkatkan potensi terjadinya banyak penyakit, seperti disentri, diare, tuberculosis, malaria dan tifus. Penyakit-penyakit ini tidak hanya merugikan negara sejumlah 50 Triliun, tetapi juga berkontribusi sebanyak 88 persen kematian anak di Indonesia. Salah satu permukiman di Jakarta Barat yang mengalami masalah kesehatan adalah Kelurahan Kalianyar. Kepadatan penduduk dan kepadatan bangunan di kelurahan ini sangat tinggi. Hal ini mengakibatkan buruknya sanitasi lingkungan, sirkulasi udara dan pencahayaan alami di hunian penduduk yang dibangun berdempetan. Angka morbiditas yang tinggi berdampak pada kualitas kehidupan di kelurahan ini. Tulisan ini mengangkat hasil riset kualitatif tentang kondisi fisik lingkungan dan aspek sosial ekonomi dan kesehatan warga penghuni pemukiman kumuh di Kalianyar. Tujuan studi adalah untuk menghasilkan solusi permasalahan tersebut di atas dengan pendekatan urban akupuntur. Analisis yang dilakukan menghasilkan usulan solusi dalam bentuk penyediaan wadah komunitas yang selain menjadi tempat edukasi dan interaksi warga juga menjadi fasilitas klinik terpadu, untuk meningkatkan kesehatan masyarakat di Kelurahan Kalianyar.